Technological capabilities of statistical indicators to support the educational policy of Russia - K. A. Avanesyan; M. A. Borovskaya; M. A. Masych; S. A. Kochkin (Новые технологии)
The implementation of educational projects and programs requires effective support through technologies for analyzing and monitoring the education system, which requires the formation of a system of regular monitoring of education development processes using statistical indicators and their use in the process of making and supporting management decisions. Insufficient use of statistical methods in assessing educational inequality focuses on the potential for the development of the education economy through the introduction of accurate, econometrically sound approaches to measuring the level of inequality observed in the distribution of human capital. With reference to the above mentioned, the authors aim to form a methodological approach to the analysis of educational inequality through the prism of applied economic analysis based on micro data from statistical surveys and monitoring for their effective inclusion in educational policy. The agenda of the fourth Sustainable Development Goal, which promotes equal and quality education for everyone plays an important role in this context. The authors identify key areas of educational inequality in the context of the Russian education system, and propose methods for calculating statistical indicators to measure them. Calculation methods for preschool education and higher education in terms of calculating statistical indicators on learning, academic performance, skills and support for at-risk and vulnerable groups are presented. Further research should contribute to the increment of new scientific knowledge for effective scientific support of educational policy. The approach proposed in the article will make it possible to organize a system of scientific research longitudinal support of the processes occurring at all levels of education in terms of the regularity of observations and analytics of the indicator system according to the developed methodology to support managerial decision-making in the development of educational policy in Russia.